Investigation of Intellectual Capital and Organisational Performance in Supply Chain Management: Modification of the Diamond Specification Model - Partiwi Dwi Astuti; Anis Chariri; Abdul Rohman (International Journal of Supply Chain Management, 2020)
Abstract—This study aims to examine the association between intellectual capital— which is described as the interrelationship between human capital, customer capital and structural capital—with organisational performance in supply chain managements of the banks and financial institutions in Bali Province, Indonesia. Data were collected using a self-administered questionnaire by considering the supply chain process. A total of 500 questionnaires was sent to general managers of banks and financial institutions in Bali Province. A total of 109 questionnaires was returned and analysed (a 21.80% response rate). The analysis was performed using covariance-based structural equation modelling with AMOS 21.0 software. The findings show that human capital is positively significantly associated with customer capital and structural capital. The findings also show that customer capital is positively not significantly associated with structural capital. Whereas, human capital, customer capital, and structural capital are positively not significantly associated with organisational performance.